Contextualizing embodied carbon emissions of concrete using mixture design parameters and performance metrics. (21st November 2022) - Helsel, Michelle A.; Rangelov, Milena; Montanari, Luca; Spragg, Robert; Carrion, Migdalia
Abstract: Multiple initiatives advocate for reducing embodied carbon (i.e., greenhouse gas emissions) associated with concrete production. Even though readily implementable strategies exist, practitioners are concerned that reducing embodied carbon emissions may adversely affect concrete performance and durability, resulting in detrimental effects from a life cycle perspective. To address such concerns, this study investigated the correlations between embodied carbon of concrete mixtures, mixture design parameters, and experimentally measured mechanical and durability properties. The analyzed datasets included 145 mixtures, featuring a variety of mixture designs from laboratory and field studies. The results indicate that the cement content is the most significant predictor of global warming potential (GWP) and that considerable GWP savings can be achieved by reducing and replacing cement without compromising performance. Clear correlations of GWP with compressive strength were not identified, while the results demonstrated that reduced GWP and increased electrically based resistivity (the utilized durability indicator) often occur in synergy.